Six sigma software development - Tayntor, Christine B. (Auerbach publications, 2003)
Revised and updated, this second edition clearly explains Six Sigma concepts and their application, maps Six Sigma concepts and tools to all aspects of system development, and proposes the use of Six Sigma tools to evaluate and improve the overall performance of the IT department. In addition to classic Six Sigma, the book introduces Design for Six Sigma (DFSS) and illustrates when and how its tools and techniques can be used to increase the robustness and reliability of a new system. It also shows how the judicious application of lean tools can reduce the complexity of IT processes, thus shortening the time needed to translate customer requirements into completed systems and increasing customer satisfaction.